An Efficient Dynamic Load Balancing Scheme for Distributed Simulations on a Grid Infrastructure - El Ajaltouni, E.; Boukerche, A.; Ming Zhang (2008 12th IEEE/ACM International Symposium on Distributed Simulation and Real-Time Applications, 2008)
Dynamic load balancing is a key factor in achieving high performance for large scale distributed simulations on grid infrastructures. In a grid environment, the available resources and the simulationpsilas computation and communication behavior may experience run-time critical imbalances. Consequently, an initial static partitioning should be combined with a dynamic load balancing scheme to ensure the high performance of the distributed simulation. In this paper, we propose a novel dynamic load balancing scheme for distributed simulations on a grid infrastructure. Our scheme is composed of an on-line network analyzing service coupled with monitoring agents and a run-time model repartitioning service. We present a hierarchical scalable adaptive JXTA service based scheme and demonstrate through simulation experiments that our proposed scheme exhibits better performance in terms of the simulation execution time.